2004
DOI: 10.1074/jbc.c300430200
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-2 Regulates Transforming Growth Factor-β Signaling

Abstract: Transforming growth factor-␤ (TGF-␤) has multiple functions including increasing extracellular matrix deposition in fibrosis. It functions through a complex family of cell surface receptors that mediate downstream signaling. We report here that a transmembrane heparan sulfate proteoglycan, syndecan-2 (S2), can regulate TGF-␤ signaling. S2 protein increased in the renal interstitium in diabetes and regulated TGF-␤-mediated increased matrix deposition in vitro. Transfection of renal papillary fibroblasts with S2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 41 publications
(48 reference statements)
0
90
0
4
Order By: Relevance
“…SDC2 is a significant upstream regulator of the TGF-ß signaling pathway (6), regulating signaling by acting as a co-receptor for growth factors. SDC2 facilitates signaling by forming a ternary complex with TGF-ß and its signaling receptors, TGFRI and TGFRII (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…SDC2 is a significant upstream regulator of the TGF-ß signaling pathway (6), regulating signaling by acting as a co-receptor for growth factors. SDC2 facilitates signaling by forming a ternary complex with TGF-ß and its signaling receptors, TGFRI and TGFRII (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Research shows that CYR61 may be regarded as both a suppressor and a promoter of cancer progression and tumour invasion. 14,17 Studies have shown that CYR61 can suppress carcinogenesis in nonsmall cell lung cancer or gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 CYR61 is an important gene in the transforming growth factor-b (TGF-b) signalling pathway and it can be activated by thrombospondin-1 through its interaction with latent TGF-b binding proteins. This interaction results in activation of TGF-b so that it can bind to its receptors, thus stimulating the Smad pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, syndecan-2 can bind and regulate the signaling of tumor growth factor-ß, and the binding is through the ectodomain of the core protein, with the heparan sulfate chains having only a minor role. The binding is independent of the cytoplasmic domain (42).…”
Section: Syndecans and Growth Factor Signalingmentioning
confidence: 97%